Auxin regulates adventitious root formation in tomato cuttings - Ling Guan (BMC Plant Biology, 2019)
Abstract Background Adventitious root (AR) formation is a critical developmental process in cutting propagation for the horticultural industry. While auxin has been shown to regulate this process, the exact mechanism and details preceding AR formation remain unclear. Even though AR and lateral root (LR) formation share common developmental processes, there are exist some differences that need to be closely examined at the cytological level. Tomato stem cuttings, which readily form adventitious roots, represent the perfect system to study the influence of auxin on AR formation and to compare AR and LR organogenesis. Results Here we show the progression by which AR form from founder cells in the basal pericycle cell layers in tomato stem cuttings. The first disordered clumps of cells assumed a dome shape that later differentiated into functional AR cell layers. Further growth resulted in emergence of mature AR through the epidermis following programmed cell death of epidermal cells. Auxin and ethylene levels increased in the basal stem cutting within 1 h. Tomato lines expressing the auxin response element DR5pro:YFP showed an increase in auxin distribution during the AR initiation phase, and was mainly concentrated in the meristematic cells of the developing AR. Treatment of stem cuttings with auxin, increased the number of AR primordia and the length of AR, while stem cuttings treated with the pre-emergent herbicide/auxin transport inhibitor N-1-naphthylphthalamic acid (NPA) occasionally developed thick, agravitropic AR. Hormone profile analyses showed that auxin positively regulated AR formation, whereas perturbations to zeatin, salicylic acid, and abscisic acid homeostasis suggested minor roles during tomato stem rooting. The gene expression of specific auxin transporters increased during specific developmental phases of AR formation. Conclusion These data show that AR formation in tomato stems is a complex process. Upon perception of a wounding stimulus, expression of auxin transporter genes and accumulation of auxin at founder cell initiation sites in pericycle cell layers and later in the meristematic cells of the AR primordia were observed. A clear understanding and documentation of these events in tomato is critical to resolve AR formation in recalcitrant species like hardwoods and improve stem cutting propagation efficiency and effectiveness.